KOMUNIKASI EKSPRESIF DENGAN METODE PECS BAGI ANAK DENGAN AUTIS - Goa, Lorentius; Derung, Teresia Noiman (Universitas Merdeka Malang, 2017)
Abstract Children with autism are children who have a nervous system disorder, caused by heredity factor. Autism is not a symptom of disease but it is a syndrome (a collection of symptoms) in which social deviations, language abilities and concerns are concerned. With regard to language skills, parents of children with autism often seek ways to allow children to speak fluently as a child in general, regardless of the child's abilities. This is the obstacle in interacting. The purpose of this study was to determine the expressive communication ability of children with autism using PECS (Picture Exchanges Communication System) method. This research uses Pre-Experimental Design method in the form of one-group pretest-posttest design. This form is used because researchers want to know the value generated by each subject after treatment is done. Method of data collection using observation method. The results showed an increase in expressive communication of children with autism after using the PECS method. The highest score was obtained by MM and LV subjects, with an increase of expressive communication value of 12 each. While KF subjects obtained an increase in value of 10 and the subject of VR 8. Thus, PECS Method could be one of the reference to improve expressive communication of children with autism. Keywords: Expressive Communication, Autism, PECS (Picture Exchanges Communication System)Â DOI : https://doi.org/10.26905/nomosleca.v3i2.2037